Sister dear - McKinnon, Hannah Mary (Mira, 2020)
"When Eleanor Hardwicke's beloved father dies, her world is further shattered by a gut-wrenching secret: the man she's grieving isn't really her dad. Eleanor was the product of an affair and her biological father is still out there, living blissfully with the family he chose. With her personal life spiraling, a desperate Eleanor seeks him out, leading her to uncover another branch on her family tree - an infuriatingly enviable half sister. Perfectly perfect Victoria has everything Eleanor could ever dream of. Loving childhood, luxury home, devoted husband. All of it stolen from Eleanor, who plans to take it back. After all, good sisters are supposed to share. And quiet little Eleanor has been waiting far too long for her turn to play."--Publisher description.